Saunders Lewis, Ordinances of the Corporation of and Acts of Assembly Relating to the City of Philadelphia 128 (1851) - (:unkn) unknown (My University, 1821)
A Supplement to an ordinance titled "an ordinance for the suspension of nuisances[.]" § 2: If any person shall fire off or discharge, wantonly and without any reasonable cause, any gun, pistol, fowling-piece or other fire-arms, at any place or from any house within the city of Philadelphia, or in any of the streets, alleys or highways of the said city, such person shall forfeit and pay for every such offence the sum of five dollars.
Keywords: DISCHARGE